Digitalization of Local Public Services: An Effectiveness Assessment of Community Satisfaction - Saputra, Dimas Arya; Suryani, Putri Amalia (Universitas Sains dan Teknologi Komputer, 2026)
The digital transformation of local public services has become a powerful weapon in the fight against bureaucracy and the battle for public approval but results still vary widely by region. The purpose of this research is to investigate the impact of the digitalization of local public services on public satisfaction. A quantitative, explanatory, cross-sectional survey was conducted among 180 users of local digital public services. The data were gathered through an online survey consisting of a Likert scale and were analyzed using Pearson correlation and simple linear regression. The research results demonstrate that the digital transformation of local public services increased public satisfaction (β = 0.721; p < 0.05) and accounted for 46.8% of the variance, indicating that digitalization played a significant role in the variation in public satisfaction. The innovative aspect of this research was to make public satisfaction the primary measure of the effectiveness of local public-sector digitalization, rather than simply measuring technology use. It offers empirical support for the development of public administration studies. It provides local governments with the opportunity to guide digitalization policies toward quality service, user experience, and sustainable public value creation, with practical implications.